Can Values-based Food Chains Advance Local and Sustainable Food Systems? Evidence from Case Studies of University Procurement in Canada and the UK - Stahlbrand, Lori (The International Journal of Sociology of Agriculture and Food, 2018)
This article asks whether the concept of values-based food chains (VBFC) can help explain and advance processes fostering sustainability transitions in the food system of the Global North. The VBFC concept is contested in the context of the author’s research into Canadian and UK university food procurement experiences designed to promote purchases of local and sustainable foods. Notwithstanding important contributions to the role of values as motivators in emerging food movements, the author argues that the formulations and conceptualizations around VBFCs are problematic because they focus too heavily on market-based differentiation as a driver of the sustainability agenda, and because they underestimate the role of oligopolistic businesses in the shaping of food supply chains. The article posits that public sector institutions have a central role to play in developing sustainable local food systems. I have coined the term ‘infrastructure of the middle’ as an alternate conceptualization, which highlights public goods and goals, and features the role of the public sector and civil society organizations, as well as farmers and other private sector enterprises.